Synthesis of Hydroxyapatite/Zinc Oxide Nanoparticles from Fish Scales for the Removal of Hydrogen Sulfide: 10.32526/ennrj/20/202100228 - Van-Pham, Dan-Thuy; Vinh Phat, Vien; Huu Chiem, Nguyen; Thi Bich Quyen, Tran; Truong Ngoc Mai, Ngo; Huynh Giao, Dang; Ngoc Don, Ta; Van Hong Thien, Doan (Environment and Natural Resources Journal, 2022)
The presence of hydrogen sulfide (H2S) is an issue for industrial processing, such as gasoline, natural gas, and biogas. In this study, hydroxyapatite (HA) nanoparticles with high purity were successfully extracted from red tilapia fish scales and used as supporting materials for zinc oxide (ZnO) to remove H2S. Various amounts of ZnO decorated on HA nanoparticles were prepared from a zinc nitrate hexahydrate precursor. Powder X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) of the ZnO/HA samples demonstrated the successful synthesis of ZnO/HA with high purity. The scanning electron microscope (SEM) image analysis confirmed the uniform deposition of ZnO on HA nanoparticles which were smaller than 245 nm. The ZnO/HA samples with different ZnO loadings (i.e., 5, 10, and 15 wt%) were used to remove H2S at room temperature. The specific surface area of HA and ZnO/HA determined by the Brunauer-Emmett-Teller (BET) method was 37.022 (m2/g) and 111.609 (m2/g), respectively. The experimental results demonstrated the highest breakthrough sulfur capacity of 26.3 mg S/g with the sorbent ZnO (15 wt%)/HA nanoparticles. This H2S adsorption capacity was the highest capacity ever achieved for ZnO/HA.Therefore, there are great possibilities for effective removal of H2S at the ambient conditions using the ZnO (15 wt%)/HA nanoparticles, where HA nanoparticles could be sustainably extracted from the abundant organic source of red tilapia fish scales.